Immunohistochemical phospho tensin tumor suppressor gene staining patterns in endometrial hyperplasias: A 2-year study - Anuradha C. K. Rao; Garima Arya; Priya J Padma (Wolters Kluwer Medknow Publications, 2011)
Background: Endometrial carcinoma is a common neoplasm associated with the female genital tract with considerable morbidity.Eendometrial hyperplasias have been widely regarded as precursor lesions. It is of importance to the pathologist to identify the subset of hyperplasias or the associated factor which could be a possible forerunner of malignancy. Phospho tensin gene (PTEN) has gained importance as one of the factors responsible. Aim: To determine the variability in PTEN expression patterns in different types of endometrial hyperplasias. Settings and Design: The study was undertaken on samples received at the Department of Pathology from 2005 to 2007. Materials and Methods: One hundred samples with 76 showing hyperplasias of different types formed the core "study group" with simple hyperplasia without atypia predominating. The rest belonged to the control groups. PTEN intensity and percentage positivity, variability in patterns of glandular and stromal expression, the number and type of PTEN null glands in different types of hyperplasia were evaluated. Statistical analyses used were Fisher's exact test based on Monte Carlo test and chi-square test. Results: Complex hyperplasia was associated with a reduction in number of strongly PTEN positive glands, with an increase in null glands, seen in clusters. Co-existing atypia was associated with the weakest staining and in fewer glands. Conclusions: PTEN expression in endometrial hyperplasias can be used as an early warning of heightened cancer risk and a potential target for preventive treatment. However, extensive research is needed along this line to conclusively establish its effectiveness.